Surgical sponge blood salvage spinning device design and testing. (18th August 2018) - Moua, Peter K.; Nguyen, Christopher L.; Piotrowski, David A.; Resch, Mitchell J.; Tabassum, Tasnia; Noonan, Kenneth; Nimunkar, Amit J.
Abstract: One method to clear intraoperative blood from the surgical field is to remove blood with surgical sponges. Currently, absorbed blood cannot be retrieved effectively and is lost. A spinning device was created to salvage red blood cells from the sponges. With this device the sponges are gently washed with saline and the resultant bloody fluid can be delivered to a cell saver to prepare it for autologous blood transfusion. In this article, we demonstrate how a novel sponge extractor can be used to extract blood from sponges. Several tests were conducted with porcine blood to optimise viable blood salvage by varying spin speed, and spin time of the device. At spin speeds greater than 1000 RPM, the blood salvaged from the device was similar to blood volumes obtained by hand wringing sponges. Cell viability testing yielded no significant differences in haemolysis for device trials compared to gently hand wringing. Spin time testing showed no significant differences in the blood salvaged at times greater than one minute. Optimal parameters for the device were determined to be a one-minute spin time at 1500 RPM.